Influence of titanium and gold platelet morphology on heat transfer in biomagnetic third-grade hybrid nanofluid flow through a vertical channel - S. Suneetha; S.R.R. Reddy; Maduru Lakshmi Rupa; T. Mahesh Kumar; Mohammed Jameel; Taoufik Saidani; Lamia Abu El Maati; Dilsora Abduvalieva; M. Ijaz Khan (Case Studies in Thermal Engineering)
This study investigates the influence of heat radiation on entropy formation in an unstable pulsatile flow of a blood-based hybrid nanofluid through a permeable conduit. Due to its high viscosity, blood is modelled as a third-grade fluid. Gold and titanium nanoparticles, known for their extensive biomedical applications, are suspended in blood as the base fluid to form the hybrid nanofluid. The third-grade fluid has been injected from the left wall at the same velocity and withdrawn from the right wall. Through the use of perturbation, the nonlinear momentum and energy equations are reduced to nonlinear ordinary differential equations. The collocation method is utilized to solve these transformed equations. Graphic images and tables depict the effects of relevant parameters and emergent variables. The Ti−Au hybrid nanofluid’s steady velocity is higher than the Ti nanofluid. The Ti nanofluid’s unsteady velocity is higher than the Ti−Au hybrid nanofluid. The findings show that when the non-Newtonian parameter increases, the entropy generation falls. At the surface where y approaches zero, increasing thermal radiation and the Darcy number of the porous media results in a higher heat transfer rate.